THE ENGLISH-LEARNING STRATEGIES OF AN INDIGENOUS ENGLISH LEARNER IN THE NORTHEAST OF THAILAND - Vincentia Aprilla Putri (University of Kuningan, 2020)
This study investigated English-learning strategies applied by an indigenous student in Amnat Charoen Province, in the Northeast of Thailand. Despite the lack of English exposure in the area, the participant, who was an English learner at a private primary school in Amnat Charoen Province, Thailand, had an excellent English ability. The data collection and analysis were done qualitatively through interviews and observations. Based on the interviews and observations, the participant was reported using both direct and indirect strategies in learning English. The dominant direct learning strategies were memory strategies and compensation strategies. The participant developed habits to summarize learning materials and use gestures to assist the speaking practice. Also, in the frame of indirect strategies, the participant applied social strategies more frequently than other indirect learning strategies. The social strategies were obviously noticeable in the consistency to practice English by interacting with foreign teachers. Further, the social learning strategies were also believed to be the most essential learning strategies developed by the participant.Keywords: learning strategies; direct strategies; indirect strategies